God in three persons a contemporary interpretation of the Trinity - Erickson, Millard John, 1932- (Grand Rapids, MI Baker, 1995)
Includes bibliographical references and indexes.
Keywords: God -- Trinity -- History of Doctrines; God -- Trinity -- Biblical teaching